Distance running performance is improved with carbohydrate intake - Doyle, J. A.; Elliott, M. B. (Medicine & Science in Sports & Exercise, 1996)
The consumption of .25 gm CHO/kg BW per 15 minute period improves endurance running performance and reduces the perception of effort in the latter stages of the effort.